2018
DOI: 10.1186/s12872-018-0896-z
|View full text |Cite
|
Sign up to set email alerts
|

Managing patients with prediabetes and type 2 diabetes after coronary events: individual tailoring needed - a cross-sectional study

Abstract: BackgroundUnderstanding the determinants associated with prediabetes and type 2 diabetes in coronary patients may help to individualize treatment and modelling interventions. We sought to identify sociodemographic, medical and psychosocial factors associated with normal blood glucose (HbA1c < 5.7%), prediabetes (HbA1c 5.7–6.4%), and type 2 diabetes.MethodsA cross-sectional explorative study applied regression analyses to investigate the factors associated with glycaemic status and control (HbA1c level) in 1083… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
3
1
Order By: Relevance
“…Secondly, statistical methods matched to the study design were used to accurately derive factors associated with diabetes or prediabetes. Finally, the study reached conclusions about the relationship between smoking and prediabetes that are inconsistent with other studies, 45 , 46 and these may provide us with some ideas for future research. Nonetheless, there are several limitations in our study.…”
Section: Discussioncontrasting
confidence: 72%
“…Secondly, statistical methods matched to the study design were used to accurately derive factors associated with diabetes or prediabetes. Finally, the study reached conclusions about the relationship between smoking and prediabetes that are inconsistent with other studies, 45 , 46 and these may provide us with some ideas for future research. Nonetheless, there are several limitations in our study.…”
Section: Discussioncontrasting
confidence: 72%
“…Sleep deprivation and sleep disorders contribute to pathophysiological changes associated with the development of T2DM, and, among diabetes, sleep deprivation contributes to elevations of HbA1c [85]. A recently published Norwegian study concluded that, along with obesity and hypertension, insomnia was the major modifiable factor associated with T2DM [86]. Aurora et al reported the bidirectional link between OSA and T2DM and concluded that early identification of obstructive sleep apnea in patients with metabolic dysfunction—including type 2 diabetes—and assessment for metabolic abnormalities in those with obstructive sleep apnea could reduce cardiovascular disease risk and improve the quality of life of patients [87].…”
Section: Discussionmentioning
confidence: 99%
“…MDAM and MTR-7 summary scores were significantly correlated with a p-value <0.001. The study by Munkhaugen, et al, (2018) had results with low Morisky scores (Score: >2 on the 8-item Morisky medication adherence questionnaire, indicating low adherence) of 9.6%, or 22 people out of 243 patients, for a p-value of 0.01.…”
Section: Resultsmentioning
confidence: 97%